Serum Anti-Helicobacter pylori IGG Antibody Test Among Patients with Diabetes: A Cross-Sectional Study - Aisha M. A. Shahlol; Eman Younis; Salwa Mahmed Ali Alfituri; Aisha M. Alfituri; Mabroukah Alzwayi; Mabroukah A. Abdullah (Indonesian Journal of Multidisciplinary Science, 2023)
Diabetes patients frequently experience numerous and serious chronic infections because of their weakened cellular and humoral immune systems. Regrettably, there is insufficient information on the prevalence of Helicobacter pylori (H. pylori) infection among diabetics, especially in southern Libya. This study aimed to determine how frequently these bacteria were infected among diabetes patients in various parts of Ubari. This study was conducted on 150 diabetic patients of both sexes, who visited the health centers in different Ubari areas. Their ages ranged from 20 to 80. Analysis of blood serum samples to measure Helicobacter pylori IgG antibodies by the enzymatic immunoassay (ELISA) and the rapid test (cassette rapid test). Biochemistry parameters such as Blood glucose concentration, cumulative glucose, ?-amylase, LDH, Serum cholesterol, Triglycerides, LDL, and HDL, as well as the blood group, were also measured. Other data collected was the body mass index. A questionnaire was used to find out some habits, such as smoking, the use of spices in food, and the type and duration of diabetes. Data showed the rate of infection with H. pylori bacteria through immunological testing was 45.33% in both sexes; however, it was significantly higher in males than females, 28% and 17%, respectively. The infection rate was found to be higher in the age group 41–60 years, and there was no significant difference in bacterial infection between patients with type I and type II diabetes (20.7 and 24.7%), respectively. Similarly, there was no effect of body mass index on the rate of infection.